M179. ALTERNATED BRAIN AND BEHAVIORAL DEVELOPMENT IN A NONHUMAN PRIMATE MODEL OF MATERNAL IMMUNE ACTIVATION. (18th May 2020) - Bauman, Melissa; Ryan, Amy; Iosif, Ana-Maria; Murai, Takeshi; Lesh, Tyler; Vlasova, Roza; Van Der Water, Judy; Styner, Martin; Kimberley McAllister, A; Carter, Cameron
Abstract: Background: Children born to women who experience infection during pregnancy have an increased risk of brain disorders with neurodevelopmental origins, including both schizophrenia (SZ) and autism spectrum disorder (ASD). Rodent models of maternal immune activation (MIA) have identified the maternal immune response as the critical link between maternal infection and aberrant brain and behavior development in offspring. The nonhuman primate MIA model provides an opportunity to maximize the translational utility of this model in a species more closely related to humans. Our previous pilot study found that rhesus monkeys (Macaca mulatta) born to MIA-treated dams developed behavioral abnormalities and increased striatal dopamine during adolescence. Here we present emerging behavioral outcomes from a larger cohort of MIA-treated nonhuman primates. Methods: A modified form of the viral mimic, Polyinosinic-polycytidylic acid (PolyIC), was delivered to a new cohort of pregnant rhesus monkeys (N=14) in the late first trimester (gestational days 43, 44, 46) to stimulate a maternal immune response. Control dams received saline injections at the same gestational time points (N=10) or were untreated (N=4). The offspring are undergoing ongoing comprehensive behavioral evaluations paired with longitudinal neuroimaging to quantify the emergence of brain and behavior pathology associated with prenatal maternal immune challenge. Results: MIA-treated dams exhibited a strong immune response as indexed by transient increases in sickness behavior, temperature and inflammatory cytokines. Although MIA offspring developed species-typical milestones and showed no overt signs of atypical interactions with mothers or peers early in development, they had significantly smaller gray matter volume in the prefrontal and frontal cortices than control offspring at 6, 12 and 24 months of age (p < 0.05). At 24 months of age, the animals were tested in a reversal learning paradigm that requires a subject to flexibly adjust its behavior when the reward-related contingencies that it has previously learned are reversed. All animals advanced and performed similarly on the training and initial discrimination phases of the test. However, on the first day of the initial reward reversal, the MIA-treated animals more frequently failed to make a choice as compared to controls (Wilcoxon two-sample test p-value = .005). These emerging data suggest that MIA-treated animals exhibit subtle impairments in cognitive processing. Additional assessments social and cognitive development, including non-invasive eye tracking data, will be presented to further explore the impact of MIA on primate behavioral development. Discussion: These findings provide new insights into the emergence of brain pathology in MIA-exposed primates and have implications for the developmental pathophysiology of human psychiatric disorders associated with maternal gestational infection.